PERBANDINGAN ANTARA PERAN JAKSA DI INDONESIA DENGAN PERAN JAKSA DI DAERAH ADMINISTRASI KHUSUS MACAO DALAM SISTEM PERADILAN PIDANA MENURUT UNDANG-UNDANG DASAR - Istiqomah Farha Anisa; Eis Libiasenti; Fitri Safira Andini; Muhamad Renaldi; Nanda Rachmad Fauzi; Muhamad Misbachul Kahfi (Pusat Riset dan Inovasi Nasional, 2023)
Macao's judicial system is rooted in the Portuguese judicial system (including Spain, Belgium and the Netherlands, all of which are rooted in the French judicial system), namely the inquisitor or non adversarial type of judiciary. is the term Magistrate is used in various systems of government and statutes to refer to the civil officers who administer the law. Both Indonesia and Macau adhere to the European continental legal system. However, in the role of the Prosecutor's Office and the Prosecutor's Office have differences and similarities in the implementation of their duties, functions and obligations. With this study of the role of the Prosecutor's Office, it is hoped that it can provide inspiration for the Attorney General's Office in Indonesia so that it can correct existing deficiencies. This research is a normative research (normative approach), that is, besides relying on normative research, the law is also coupled with a theoretical approach. Furthermore, in analyzing the data, a qualitative approach was used and it was also based on library-based studies, which means that the materials needed for research must be available in libraries, archives and databases, laws and other documents.